PERTANGGUNGJAWABAN PIDANA ORANG DENGAN BERKEPRIBADIAN GANDA (DISSOCIATIVE IDENTITY DISORDER) YANG MELAKUKAN TINDAK PIDANA PEMBUNUHAN - Rotarigma, Novi Novia; Mangesti, Yovita Arie (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The purpose of this legal study is to ascertain how criminal liability for murderers with multiple personalities (Dissociative Identity Disorder) is regulated.This study employs a normative approach, which means that it looks at primary, secondary, and tertiary legal materials found in libraries or other secondary sources.data gathered from books of literature, existing research, and relevant legislation.The study’s findings lead us to the conclusion that because they have fulfilled the element of criminal responsibility, people with multiple personalities (Dissociative Identity Disorder) can be punished for the murder they have committed.The application of the idea of accountability in strict liability is the form of criminal responsibility. This allows the offender to be sentenced to prison in accordance with the threat in Article 338 of the Criminal Code, which deals with murder